Implementasi Model Waterfall Pada Pembangunan Sistem Informasi Keuangan Proyek - Riska Aryanti; Diah Puspitasari; Rachilsyah Ramdhani Efendi; Rizqi Nur Esmeralda (Universitas Bina Sarana Informatika, 2022)
In the digital era like today, technology is developing very rapidly. Computers have become a major requirement in business processes today. PT Suma Karya Gemilang is a company engaged in the construction sector. PT Suma Karya Gemilang in running its business is still not computerized such as submitting funds and making project expense reports. The impact of a system that has not been computerized causes ineffectiveness in work, frequent unintentional errors, frequent buildup of unprocessed documents, resulting in documents being easily lost and damaged if not processed quickly, making project expense reports often writing errors and inaccurate in the making. So that the design of a project financial information system with the Waterfall development method is a solution to the problems that exist at PT Suma Karya Gemilang. With a computerized system, the work process becomes more efficient and effective in supporting all company activities. The results obtained by using a computerized system reduce writing errors, report generation becomes accurate and effective, with the use of document databases becoming more organized and not piling up. Overall, a computerized system is much better in all aspects than a non-computerized system.